PERLINDUNGAN HUKUM HAK CIPTA TERHADAP PENCIPTA LAGU YANGLAGUNYA DIGUNAKAN TANPA IZIN DI APLIKASI TIKTOK - I Putu Andika Pratama; Ni Luh Gede Putri Laksmi Brata; Ni Ketut Putri Sri Ayu Lestari (Jurnal Ilmiah Raad Kertha, 2023)
Tiktok is one of the most popular and popular applications in the world, this Tiktok takes songs that have been cut automatically, which are made attractive with funny sounds and styles, then these songs can be shared by other people with their own styles. The formulation of the problems in this study are: (1) What is the form of legal protection for song owners whose songs are used without permission and (2) What are the legal consequences of TikTok application users using songs without permission. This research is a doctrinal research used primary, secondary and tertiary legal materials. The technique of collecting legal materials is carried out using a statue approach. The results of this research are, first, the Tiktok application itself already has Terms of Service or terms of use related to content uploaded to the application contained in User Generated Content. Second, related to the use of songs uploaded by users of the Tiktok application without permission, copyright holders can sue, because songs uploaded by users of the Tiktok application are truncated. In the tiktok application itself, there are Terms of Service contained in the User Generated Content section.